TRADISI PEMBACAAN SURAH AL-MULK DI MAJELIS TA’LIM RAUDHOTUL ILMI PALEMBANG: - Muhammad Ali .; Uswatun Hasanah; Beko Hendro (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2021)
This article discusses the implementation of the reading of Surah al-Mulk at the Raudhotul Ilmi Palembang Ta'lim Assembly and the views of the Raudhotul Ilmi Palembang Ta'lim congregation on the reading of Surah al-Mulk as well as an analysis of Max Weber on the recitation of surah al-Mulk at the Raudhotul Ilmi Palembang Ta'lim Assembly. This type of research is a field research (Field Research), the type of data used is qualitative with the study of living hadith. This study uses Max Weber's theory of social action related to four actions, namely, traditional action, affective action, value rationality action and instrumental rationality action. The subjects of this research are caregivers, administrators, ustaz and Jama'ah Majelis Ta'lim Raudhotul Ilmi Palembang. The data collection technique used observation by observing and paying attention to the implementation of the tradition of reading surah al-Mulk at the Raudhotul Ilmi Palembang Ta'lim Assembly. While the interview data, the researchers interviewed twelve Jama'ah as respondents, while the documentation was equipped with books, photos and books related to the research. Meanwhile, data analysis uses descriptions and explanations. This study found that the Jama'ah of the Raudhotul Ilmi Palembang Ta'lim Assembly was enthusiastic about the tradition of reciting surah al-Mulk in the Assembly. The congregation of the assembly is of the view that having the reading of Surah al-Mulk before starting the assembly is a good and good thing as a form of imitating the Prophet Muhammad. The congregation of the assembly supported this activity because of the benefits of reading it as a barrier from the torment of the grave and there were some congregations who routinely read Surah al-Mulk. It can be said that the response of the congregation of the assembly tends to know the values ​​contained in the hadith of reading surah al-Mulk. This shows that the living hadith in the congregation of the assembly was carried out and the Raudhotul Ilmi Palembang Ta'lim Assembly fulfilled Max Weber's theory of social action.